Conservative Islamic factions vs. secular nationalists: toward a civil contestation in democratic Indonesia - Peter Suwarno (Indonesian Journal of Social Sciences, 2021)
This paper describes how Indonesia’s presidents have delt with Islamist and secular nationalist political contestation since the preparation of Indonesian independence and how the current president compares. Soekarno’s initial reliance on civil discourse ended in his autocratic decree that banned the Indonesia’s most powerful Islamic party (Masyumi). Soeharto’s initial iron-fist approach ended up meeting some Islamic demands. B.J. Habibie helped transformed Indonesia through a democratic election in 1999, but the leader of the winning party, Megawati was defeated in the parliament that elected a pluralist Muslim cleric, Gus Dur. Gus Dur’s administration, ended by the central axis, suggests that liberal democratic processes cannot be applied in an increasingly conservative Muslim majority country. Megawati lost, partly because she is a female president unpopular among the Islamists, while SBY was sympathetic toward the Islamist’s demands, enhancing the “conservative turn.” Jokowi has used discursive and legal approaches to promote Pancasila in challenging the hardline Islamic demands, enabling him to ban HTI and FPI and to implement the speech freedom-limiting laws, leading to criticisms and the decline in the 2020 Indonesia's Democracy Index. Jokowi’s expansion of these laws to maintain unity and stability may be deemed an “authoritarian turn,” but I argue that it may be more appropriately called “the Pancasila turn.” In framing and analyzing Jokowi’s laws as a Pancasila turn, I am arguing in this paper that this lays the foundation for a more equal, civil, and democratic contestation.